2023
DOI: 10.1039/d2cp05939h
|View full text |Cite
|
Sign up to set email alerts
|

Chiral symmetry breaking induced by energy dissipation

Abstract: Spontaneous chiral symmetry breaking is observed in a wide variety of systems on very different scales, from the subatomic to the cosmological. Despite its generality and importance for a large...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…The diverse proportions of enantiomeric crystals can be understood by applying thermodynamic principles [ 51 ]. To illustrate this, it is essential to calculate the free energy change in the process.…”
Section: Symmetry Breaking Across Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…The diverse proportions of enantiomeric crystals can be understood by applying thermodynamic principles [ 51 ]. To illustrate this, it is essential to calculate the free energy change in the process.…”
Section: Symmetry Breaking Across Scalesmentioning
confidence: 99%
“…Experiments consisting of evaporating the solvent to obtain NaClO 3 crystals [ 34 ], performed by stirring the sample, revealed a significant disproportion in the concentrations of both enantiomeric crystals of NaClO 3 . In a recent study, it was found that the energy dissipation rate of the phase change and heat transfer determines the enantiomeric excess percentage in the case of enantiomeric crystals of NaClO 3 [ 51 ]: and are the nucleation rates of both enantiomers, whereas and are the driving force (fugacity difference between liquid and solid state). Moreover, is the thermal conductivity of the system and T is the temperature.…”
Section: Symmetry Breaking Across Scalesmentioning
confidence: 99%
“…Symmetry breaking implies the spontaneous generation of enantiomeric excess from an equimolecular mixture of two enantiomers through the application of an external stimulus, usually stirring, solvent, a magnetic field or light. 98 Symmetry breaking is often observed in the field of crystallization upon the application of controlled stirring. Following this strategy, Ribo ´and coworkers were able to generate chiral aggregates from diluted solutions of 4-sulfonatephenylporphyrins by biasing the stirring direction.…”
Section: Symmetry Breaking In Supramolecular Polymers: Chiral Structu...mentioning
confidence: 99%
“…Dissipative chemical systems play a central role in the bottom‐up emergence of complex phenomena, such as pattern formation, transient gelation, and (collective) motion. [ 1–3 ] Characteristic of dissipative systems is the requirement of constant input of energy, for example, by an external light source or conversion of “fuel” molecules via a chemical reaction. [ 4–11 ] While synthetic matter usually resides in a single state that is determined by thermodynamic equilibrium, the constant dissipation of energy unlocks out‐of‐equilibrium configurations.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4–11 ] While synthetic matter usually resides in a single state that is determined by thermodynamic equilibrium, the constant dissipation of energy unlocks out‐of‐equilibrium configurations. [ 1,12,13 ] As a result, dissipative systems are able to reversibly switch between a variety of configurations as they adapt their structure to external stimuli. [ 14–16 ] These principles provide a foundation for the construction of adaptive chemical systems with properties mimicking those of living organisms, which are themselves dissipative in nature.…”
Section: Introductionmentioning
confidence: 99%